Pemberdayaan Masyarakat Berbasis KKN dalam Pencegahan Stunting pada Ibu Hamil di Desa Silau Malaha - Egi Regi Prayoga; Dhita Lutfiah; Hana Nafisah; Eliska Eliska (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
Stunting is a condition where a person has a height and body length that is less / not in accordance with body conditions in general. The impact of stunting itself is a decrease in learning and cognitive achievement abilities. The World Health Organization or WHO states that around 20% of stunting begins when the baby is still in the womb. This is also caused by the intake of the mother when it is of poor quality and not nutritious, which results in the fetus being malnourished and this is also continuous during the period of stunted growth until the time of birth. The solutions needed to overcome stunting include specific nutrition interventions, namely pregnant women. The purpose of this study is an effort to prevent stunting in pregnant women through a health seminar in Silau Malaha Village. This method of community service is with a pre-test before the class meeting of pregnant women and providing counseling, training and education to pregnant women during their pregnancy is carried out after that a post test is carried out in order to find out the success of the class for pregnant women. The results showed that some of the seminar participants did not know about stunting prevention before the seminar was held, especially for young mothers who had just become pregnant, but after the counseling from the post test results almost all participants knew about stunting prevention after the seminar was held. It is proven by the results of the table obtained from the questionnaire given to the stunting seminar participants.